The Relationship between Premium Beer Brand Attributes and Brand Loyalty – An Exploratory South African Study - Peter Kaupa, Stewart; Govender, Krishna (British Journal of Marketing Studies, 2015)
This paper reports the findings of an exploratory study conducted among a convenience sample of 300 premium beer consumers selected from two major cities in KwaZulu-Natal, South Africa. South African Breweries (SAB), the largest brewery in South Africa has been struggling to compete in the premium beer market as a result of more brands competing in the premium beer market which is the most attractive segment of the beer market. This paper aimed at exploring the factors that attract consumers to premium beer brands. It was ascertained that the crispiness of the beer, superior, unique taste and, the price of the beer brand ate important factors.The implications of the above for the SAB, is that premium beer market is a highly competitive market hence, marketing strategies should take into consideration the factors which attract the consumers to a brand. For the SAB to gain a competitive advantage, it needs to design marketing strategies that will differentiate its premium beer brands on the basis of the important factors that attract consumers, namely price, beer quality, crispiness and taste.